The Impact of Bariatric Surgery on Psychological Health - Jeremy F. Kubik; Richdeep S. Gill; Michael Laffin; Shahzeer Karmali (Journal of Obesity)
Obesity is associated with a relatively high prevalence of psychopathological conditions, which may have a significant negative impact on the quality of life. Bariatric surgery is an effective intervention in the morbidly obese to achieve marked weight loss and improve physical comorbidities, yet its impact on psychological health has yet to be determined. A review of the literature identified a trend suggesting improvements in psychological health after bariatric surgery. Majority of mental health gain is likely attributed to weight loss and resultant gains in body image, self-esteem, and self-concept; however, other important factors contributing to postoperative mental health include a patient’s sense of taking control of his/her life and support from health care staff. Preoperative psychological health also plays an important role. In addition, the literature suggests similar benefit in the obese pediatric population. However, not all patients report psychological benefits after bariatric surgery. Some patients continue to struggle with weight loss, maintenance and regain, and resulting body image dissatisfaction. Severe preoperative psychopathology and patient expectation that life will dramatically change after surgery can also negatively impact psychological health after surgery. The health care team must address these issues in the perioperative period to maximize mental health gains after surgery.